Liraglutide Promotes Osteoblastic Differentiation in MC3T3-E1 Cells by ERK5 Pathway - Yue Sun; Yuzhen Liang; Zhengming Li; Ning Xia (International Journal of Endocrinology)
Liraglutide is a glucagon-like peptide-1 analogue widely used in the treatment of type 2 diabetes mellitus. However, the effects of liraglutide on osteoblast proliferation and differentiation in MC3T3-E1 cells have not been fully elucidated. In the present study, the promoting effects of liraglutide were investigated in MC3T3-E1 cells. The results indicated that cell viability was affected following the treatment of the cells with different concentrations of liraglutide (0, 10, 100, and 1000 nM) at different time periods of culture (24, 48, and 72 h). Moreover, the activity levels of alkaline phosphatase and the number of mineralized nodules in MC3T3-E1 cells were significantly increased following treatment with 100 nM liraglutide. The mRNA and protein levels of Col-1, OPG, and OCN in MC3T3-E1 cells were also markedly increased following 100 nM liraglutide treatment compared with those of the control group. The expression levels of the ERK5 signaling pathway key proteins (MEK5, p-ERK5, ERK5, and NUR77) were increased following liraglutide treatment in MC3T3-E1 cells, and the gene expression levels of the ERK5 signaling pathway were also elevated. Moreover, the ERK5 inhibitor XMD8-92 significantly decreased the expression levels of p-ERK5 and NUR77 as well as the proliferation of osteoblasts. However, these changes could be rescued by liraglutide to some extent. Therefore, these results revealed that liraglutide may promote osteoblastic differentiation and proliferation in MC3T3-E1 cells via the activation of the ERK5 signaling pathway.